7.4 Paediatric Respiratory Infection and Immunology 2015
DOI: 10.1183/13993003.congress-2015.oa1993
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence analysis and diagnosis of primary ciliary dyskinesia with radial spoke defects

Abstract: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous recessive disorder caused by several distinct defects in genes responsible for ciliary beating, leading to defective mucociliary clearance often associated with randomization of left/right body asymmetry. Individuals with PCD caused by defective radial spoke (RS) heads are difficult to diagnose owing to lack of gross ultrastructural defects and absence of situs inversus. Thus far, most mutations identified in human radial spoke genes (RSPH) are lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…H irst et al [ 100 ] demonstrated electron microscopy changes in some cilia from some patients with conditions included under the umbrella term ciliopathies (genetic disorders of non-motile cilia) ( figure 1 ). A multinational team used immunofluorescence to explore functional correlates of genetic mutations in patients with PCD and proposed this approach would be valuable in diagnosis of patients with loss-of-function mutations and missense variants [ 101 ]. Another condition associated with significant respiratory morbidity is ataxia telangiectasia.…”
Section: Infection and Immunitymentioning
confidence: 99%
“…H irst et al [ 100 ] demonstrated electron microscopy changes in some cilia from some patients with conditions included under the umbrella term ciliopathies (genetic disorders of non-motile cilia) ( figure 1 ). A multinational team used immunofluorescence to explore functional correlates of genetic mutations in patients with PCD and proposed this approach would be valuable in diagnosis of patients with loss-of-function mutations and missense variants [ 101 ]. Another condition associated with significant respiratory morbidity is ataxia telangiectasia.…”
Section: Infection and Immunitymentioning
confidence: 99%